Invincible yuanfen ? - Hélène Bloch (Ateliers d'Anthropologie)
In Chinese, the term yuan or yuanfen designates the predestined affinity a person can have for another entity, which might be another person, a place, or even an object. Yuanfen seems to be both the invisible cause and the relational consequence of a first meeting. This notion is a topos that is so common in love songs and unexpected meetings in everyday life that the range of situations in which it can play a part is often ignored, to the advantage of an instrumental use that aims to illustrate a uniquely Chinese way of considering social relations. Beginning with a critical overview of works on yuan and yuanfen, as well as ethnographic research conducted in Sichuan since 2016, this article will explore the different contexts in which this notion fits, in order to take into account the complexity of the registers that speakers handle and the pragmatic uses they can make of these terms.